Empowering Farmers through Digital Marketing in Delanggu Village, Klaten, Central Java - Ayu Puspitasari, Sylvatera; Gilang Titah Ramadhan; Sutanto (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
Digital marketing is an effort to market products and services to consumers through digital media which is widely used by almost every group. Empowerment through digital marketing accompanied by startup Ecokarsa helps the Sanggar Rojolele farmer group in Delanggu village to introduce their harvest, namely Rojolele rice. Rojolele rice is a special premium rice variety that is difficult to market conventionally. With digital marketing, Rojolele rice can be found by the right consumers and can be fully absorbed. Utilizing digital marketing, the Sanggar Rojolele farmer group can experience significant profits by selling rice with operational costs calculated compared to previously only selling grain to middlemen at low prices. Intense training and mentoring were carried out by startup Ecokarsa for one year to guide the Sanggar Rojolele farmer group with the hope that after one year of mentoring, Sanggar Rojolele could market Rojolele rice products independently. Mentoring and training activities do not only focus on products but also on introducing villages and rice cultivation activities, with the hope that Delanggu village can be widely known.